2006
DOI: 10.1002/art.22093
|View full text |Cite
|
Sign up to set email alerts
|

Durometry for the assessment of skin disease in systemic sclerosis

Abstract: Objective. To examine the validity of a durometer to objectively measure skin hardness in systemic sclerosis (SSc), and to compare digital durometry with the modified Rodnan skin score (MRSS) and ultrasonography. Methods. Patients with SSc and healthy controls underwent durometry measurements in 3 assessments: a Latin square experiment to establish durometry's intra-and interobserver reliability compared with skin scoring (5 SSc, 1 control); a longitudinal cohort to assess sensitivity to change in skin hardnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 20 publications
8
104
1
4
Order By: Relevance
“…Durometry yields precise data about tissue firmness and can detect subtle differences in skin texture. [20][21][22][23][24][25] In this study, durometry revealed that skin injected with 3D MA-HA had similar firmness as the control groups and no changes over the course of 30 days were noted (Fig. 6).…”
Section: Discussionsupporting
confidence: 50%
“…Durometry yields precise data about tissue firmness and can detect subtle differences in skin texture. [20][21][22][23][24][25] In this study, durometry revealed that skin injected with 3D MA-HA had similar firmness as the control groups and no changes over the course of 30 days were noted (Fig. 6).…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, Kissin et al demonstrated that durometry enables detection of even minor changes in skin hardness over time [24]. For our investigations we used a new durometer and observed – in line with previous studies – that durometry is painless and can be easily performed [23,24,25].…”
Section: Discussionsupporting
confidence: 60%
“…In earlier investigations durometry has been proven to be reliable in the assessment of morphea [23,24,25]. Moreover, Kissin et al demonstrated that durometry enables detection of even minor changes in skin hardness over time [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is an anisotropic (force response is dependent on the force direction) and a nonlinear material [1][2][3]. Several studies have identified that human skin's mechanical behavior is dependent on a variety of factors, such as age, gender, health and weight of the donor, as well as the location of the site and its orientation [1,2,[4][5][6][7][8]. The use of human skin in test situations may potentially make it difficult to analyze any experimental results and repeating of the experiment would be problematic [9].…”
Section: Introductionmentioning
confidence: 99%